ANALISIS KESALAHAN BERBAHASA INDONESIA PADA SPANDUK DI MEDAN - Vanessa Purba; Hesti Lubis; Jansen Sinabutar; Khaidar Aswan; Melia Nabila; Rensus Sijabat; Rosalia Panggabean; Ita Khairani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze errors in the Indonesian language found on banners in public spaces. The background of this study is based on the fact that language usage that does not conform to the rules of proper and correct Indonesian is still frequently encountered, whether in terms of spelling, word choice, or sentence structure. The method used in this study is qualitative descriptive, employing data collection techniques involving the documentation of banners distributed across various locations. The data obtained were then analyzed based on linguistic rules referencing the General Guidelines for Indonesian Spelling (PUEBI). The results of the study indicate that the most prevalent errors include spelling errors (such as the use of capital letters and punctuation), word choice errors (diction), and sentence structure errors that result in unclear or ambiguous meaning. Additionally, the use of mixed language and non-standard language was found to be inappropriate in formal contexts. The conclusion of this study is that public awareness regarding the proper use of Indonesian language on banners remains low. Therefore, efforts are needed to improve understanding and promote the correct and proper use of Indonesian so that information conveyed through banners can be more effective, clear, and communicative.